Analysis on EFL teachers pedagogical problems at sampaga mamuju - Hafid, Abd Gafur; Amiruddin, Amiruddin; Satriani, Satriani (Jurnal Madako Education, 2023)
This research investigated the pedagogical problems of EFL teaching practice in the rural area of Sampaga, in Mamuju. This research aimed: 1) To find out the EFL teachers’ pedagogical problems at Junior High School in Sampaga, Mamuju; 2) To find out how the EFL teachers solve the pedagogical problems at Junior High School in Sampaga, Mamuju. The research employed a descriptive qualitative design in the context of a case study. The participants were three Junior High School English teachers in Sampaga, Mamuju. The data were collected through interviews and observation. The result of the research showed there are five EFL teachers’ pedagogical problems found: 1) Very low ability to make lesson plans, 2) Less varied and innovative learning materials used in teaching, 3) Lack of up-to-date teaching methods and varied activities, 4) Limited knowledge of ICT, and 5) Lack of understanding of authentic assessment. This research also proposed ways to solve the problems based on the EFL teachers, as follow: 1) To increase the role of MGMP (Musyawarah Guru Mata Pelajaran) as a forum for teachers to share knowledge and skills, 2) To encourage Regional Education Authorities to carry out teacher development activities in line with technological developments, 3) To ask the Government to provide more chance for teacher to develop themselves through Teacher Professionalism Training Program or continue to higher education.